Step-by-step explanation
We have the following pair of functions:
![\begin{gathered} f(x)=x^3+6x \\ g(x)=√(8x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hlkz8rchowuwzetage58w2dijakx2rjqhj.png)
And we need to find (fog)(2). In order to do this we can start by calculating the composite function (fog)(x)=f(g(x)). Its expression is given by taking the equation of f(x) and replacing x with the expression of g(x). Then we get:
![\begin{gathered} (f\circ g)(x)=f(g(x))=g(x)^3+6g(x)=(√(8x))^3+6√(8x) \\ (f\circ g)(x)=(√(8x))^3+6√(8x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uqxej6i6m3g2jq19xp98znhzvhp2swy07h.png)
We need to find (fog)(2) so we just need to take x=2 in the equation above:
![\begin{gathered} (f\circ g)(2)=(√(8\cdot2))^3+6√(8\cdot2) \\ (f\circ g)(2)=(√(16))^3+6\cdot√(16) \\ (f\circ g)(2)=4^3+6\cdot4 \\ (f\circ g)(2)=64+24 \\ (f\circ g)(2)=88 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p2vcbcuelvl5t4zbuub8e7kri7ued4a3x7.png)
Answer
Then the answer is 88.